Optimization of Water and Nutrient Requirement through Drip Fertigation in Aerobic Rice - Kombali, Gururaj; Nagaraju; Rekha, B.; Sheshadri, T.; Thimmegowda, M. N.; Mallikarjuna, G. B. (International Journal of Bio-resource and Stress Management, 2023)
A field experiment was conducted during Kharif 2012 at Zonal Agricultural Research Station, Bengaluruin red sandy loam soil (pH-6.9; OC-0.6%) with medium available nitrogen (348 kg ha-1), phosphorous (36.13 kg ha-1) and potassium (244 kg ha-1) to optimize water and nutrient requirement of aerobic rice (Oryza sativa L.) through drip fertigation. The experiment was laid out in Randomized Complete Block Design (RCBD) with 15 treatments. The variety used was MAS 946-1. Drip fertigation significantly influenced the growth, yield, water productivity and nutrient use efficiency (NUE) in aerobic rice. The results revealed that drip fertigation at 1.5 PE up to maturity with 100% RDF through water soluble fertilizers (WSF) registered higher water use (706 mm) and significantly highest water productivity (78.1 kg ha-cm-1) by recording higher grain (6598 kg ha-1) and straw yield (11084 kg ha-1) over surface irrigation with soil application of fertilizers (3467 and 5995 kg ha-1, respectively). Same treatment also noticed higher number of tillers hill-1 (48.13) and higher dry matter production (118.40 g hill-1) by saving 45% of irrigation wateras that of surface irrigation. Dripfertigation at 1.5 PE up to maturity with 50% RDF through WSF has recorded higher nitrogen (98.3 kg kg-1), phosphorus (196.7 kg kg-1) and potassium (196.7 kg kg-1) use efficiency. However, increased nutrient use efficiency (NUE) was observed with reduced nutrient levels.